20 Centimeter Per Year: A Visual Pedagogy Method for Participatory Learning - Nur Wulan Dari (Humaniora, 2025)
Debates on alternative education and visual methods in anthropology and the humanities have questioned the dominance of text-based, classroom-centred pedagogy, highlighting instead situated, embodied, and affective forms of learning. Within this discourse, the documentary film Legiun Tulang Lunak – 20 Centimeter Per Year emerges as both a research process and a pedagogical experiment. Initiated to mark Hysteria’s 20-year journey, the film was developed collaboratively, with the author acting simultaneously as ethnographer and director, providing funding, creative teams, and equipment, thereby shaping a particular configuration of authorship and intervention. Employing participant observation, filming, and interviews, the project examined participants’ critical reflections on PekaKota Institute’s environmental activism and art-based social critique. Rather than presenting positivistic findings, this empirical report from the ethnographic filming advances methodological insights: visual practice enabled situated learning, affective engagement, and critical reflection that exceeded conventional classroom or textual pedagogies. The film reveals how political awareness and knowledge transmission unfold through embodied, collective, and sensory encounters. These findings contribute to discussions on alternative education, qualitative methodology, and the role of ethnographic film as a critical research practice in the humanities.